Lewis acid-catalyzed reactions of alcohol pro-electrophiles as novel strategies for C-C and C-N bond formation - Rao, Weidong (2010)
The work in this thesis was undertaken in Chemistry and Biological Chemistry, School of Physical and Mathematical Sciences in Nanyang Technological University from August 2006 to June 2010 under the supervision of Asst Prof Philip Wai Hong Chan. The work of this thesis has been directed toward the establishing of new Lewis acids catalyzed reaction of alcohol pro-electrophiles as novel strategies for C-C and C-N bond formation. This thesis is divided into four parts: Part I consists of Chapter I, which give an introduction of Lewis acid catalyzed reactions of alcohol pro-electrophiles, including several type of alcohols, such as allylic alcohols, propargylic alcohols, benzylic alcohols and α-cyclopropyl alcohols. Part II is aimed at exploring new strategies for C-C bond formation employing alcohols as pro-electrophiles. Chapter II addressed the gold-catalyzed allylic alkylation of aromatic and heteroaromatic compounds with allylic alcohols. In Chapter III, a novel strategy to highly conjugated indenes involving unexpected iron(II) chloride-catalyzed dimerization of 1,1,3-trisubstituted-prop-2-yn-1-ols was described. Part III exploring new strategies for C-N bond formation employing alcohols as pro-electrophiles. Chapter IV detailed the gold-catalyzed tandem amination/ring expansion of cyclopropyl methanols with sulfonamides as an expedient route to pyrrolidines. The method was shown to be applicable to a broad range of cyclopropyl methanols and sulfonamide substrates. In Chapter V, ytterbium(III) triflate-catalyzed ring opening of substituted1-cyclopropyl-2-propyn-1-ols with sulfonamides as an efficient synthetic route to conjugated enynes is described.